2015
DOI: 10.1371/journal.pone.0118188
|View full text |Cite
|
Sign up to set email alerts
|

Kuwanon V Inhibits Proliferation, Promotes Cell Survival and Increases Neurogenesis of Neural Stem Cells

Abstract: Neural stem cells (NSCs) have the ability to proliferate and differentiate into neurons and glia. Regulation of NSC fate by small molecules is important for the generation of a certain type of cell. The identification of small molecules that can induce new neurons from NSCs could facilitate regenerative medicine and drug development for neurodegenerative diseases. In this study, we screened natural compounds to identify molecules that are effective on NSC cell fate determination. We found that Kuwanon V (KWV),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 76 publications
(76 reference statements)
0
37
0
Order By: Relevance
“…NPCs were cultured as previously described (23). Animal experiments were performed in strict accordance with the Chung‐Ang University and the National Institutes of Health (Bethesda, MD, USA) Guide for the Care and Use of Animals.…”
Section: Methodsmentioning
confidence: 99%
“…NPCs were cultured as previously described (23). Animal experiments were performed in strict accordance with the Chung‐Ang University and the National Institutes of Health (Bethesda, MD, USA) Guide for the Care and Use of Animals.…”
Section: Methodsmentioning
confidence: 99%
“…However, only a few studies have focused on the role of chalcone derivatives on modulation of miRNAs. Rubone (10), isoliquiritigenin (11), and kuwanon V (12) modulate miR-34a, miR-25, miR-9, miR-29a and miR-181a, respectively with potent biological actions. Among these small molecules, Xiao et al first reported rubone, a chalcone analog, as a miR-34a modulator for the inhibition of hepatocellular carcinoma (HCC) growth (10).…”
Section: Introductionmentioning
confidence: 99%
“…CTX0E03 cells were exquisitely susceptible to OA cytotoxicity. DMSO as vehicle does not affect CTX and NS cell viability compared to culture media or PBS (data not shown) (Kong et al, 2015). OA treatment in primary rat cortical neurons resulted in an increased number of mature lysosomes and induced neuronal cell death (Cho et al, 2013).…”
Section: Discussionmentioning
confidence: 89%